An Exploration of Professional U.S.-Based Basketball Players Competing in Turkey. Issue 1 (2nd January 2023) - Koba, Timothy H.; Nagel, Mark S.; Watanabe, Nicholas M.; Yan, Grace; Southall, Richard M.; Kidd, Victor K.
Abstract: In the wake of the 1992 Barcelona Summer Olympic Games, basketball experienced a surge in popularity as an international sport. Recently, to field more competitive teams, professional leagues around the world have begun to recruit international players, particularly those from the United States (U.S.). Though most leagues still maintain strict caps on the number of players from a single country on a roster, the Turkey Basketball Federation (TBF) recently altered its rules to permit more international players, presenting American players greater opportunities to pursue a lucrative playing career in Turkey. Given the change in labor market characteristics, this paper examines the 102 U.S. players on 2017–2018 Turkey professional basketball rosters. Descriptive statistics for collegiate performance are presented, as well as logistic regression and network analyses that indicate players' college choice was a crucial factor in their international professional career trajectory with collegiate conference acting as a bridge to a professional career in Turkey. These results provide context for researchers and practitioners in understanding the player statistics, social and cultural forces related to U.S.-professional basketball players in Turkey.